Progress of Research into Novel Drugs and Potential Drug Targets against Porcine Pseudorabies Virus - Mo Zhou; Muhammad Abid; Shinuo Cao; Shanyuan Zhu (Viruses, 2022)
Pseudorabies virus (PRV) is the causative agent of pseudorabies (PR), infecting most mammals and some birds. It has been prevalent around the world and caused huge economic losses to the swine industry since its discovery. At present, the prevention of PRV is mainly through vaccination; there are few specific antivirals against PRV, but it is possible to treat PRV infection effectively with drugs. In recent years, some drugs have been reported to treat PR; however, the variety of anti-pseudorabies drugs is limited, and the underlying mechanism of the antiviral effect of some drugs is unclear. Therefore, it is necessary to explore new drug targets for PRV and develop economic and efficient drug resources for prevention and control of PRV. This review will focus on the research progress in drugs and drug targets against PRV in recent years, and discuss the future research prospects of anti-PRV drugs.